2019
DOI: 10.1007/s00238-019-01581-3
|View full text |Cite
|
Sign up to set email alerts
|

Muscle electrical activity after perforator flap surgery: a pilot cohort study

Abstract: Background Perforator flaps surgery barely damages underlying muscle function, but only clinical qualitative evidences exist about muscle preservation after surgical dissection. We have employed for the first time electromyography and nerve conduction studies in evaluating the latissimus dorsi electrical muscle function after thoraco-dorsal artery perforator flap dissection in a retrospective cohort study. Methods We included ten consecutive patients requiring axillary reconstruction with thoraco-dorsal artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…3,4 As any other perforator flaps, TDAP flap has the great benefits of preserving muscle integrity and decreasing postoperative donor site seromas and shoulder-related sequelae. 5,6 In 2004, Hamdi et al reported the first four cases of partial breast reconstruction with a TDAP flap, while in 2007 Ortiz et al described the first successful experience of implant-based breast reconstruction combined with a TDAP flap.…”
mentioning
confidence: 99%
“…3,4 As any other perforator flaps, TDAP flap has the great benefits of preserving muscle integrity and decreasing postoperative donor site seromas and shoulder-related sequelae. 5,6 In 2004, Hamdi et al reported the first four cases of partial breast reconstruction with a TDAP flap, while in 2007 Ortiz et al described the first successful experience of implant-based breast reconstruction combined with a TDAP flap.…”
mentioning
confidence: 99%
“…The choice between a pedicled and a "free" microvascular ap depends on the type of the defect and on the personal surgical expertise [56,57]. In a recently published meta-analysis [54], free-aps and pedicled propeller aps did not show a signi cant difference in terms of overall failure rate (3,9% vs 2,8%, respectively) as well as the "coverage failure" rate (5.2% vs 2.9%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…It can be argued that the use of pedicled propeller flaps 17 might be a better option compared with PB muscle flap, being less invasive and sparing the muscle. 18 Nevertheless, local fasciocutaneous flaps showed a complication rate of 25.2% in the meta-analysis performed by Bekara et al, 4 with a 3.5% of total flap loss and 10.2% of partial flap loss.…”
Section: Discussionmentioning
confidence: 98%